Destigmatisation within the HIV/AIDS pandemic : wowards a pastoral anthropology of embodiment - Washington, Vanessa Marie (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MTh (Practical Theology and Missiology))--University of Stellenbosch, 2010.